Adjustable Dual Muscle Speculum for Simplified Placement of a 350 Baerveldt Implant. Issue 7 (July 2017) - Grover, Davinder S.; Fellman, Ronald L.
Abstract : The authors have designed a muscle hook speculum that simultaneously allows the surgeon to isolate and expose both rectus muscles (either the superior and temporal or medial and inferior) for ease of placement of a 350-mm 2 Baerveldt implant. This instrument facilitates the exposure and subsequent placement of either a superior-temporal tube or an infero-nasal tube in a more independent manner. By using the dual muscle hook speculum, an individual surgeon, without a glaucoma-trained assistant, can hook typically both the superior and lateral recti muscles while gaining simultaneous exposure of the quadrant. The purpose of this report is to describe the instrument, how it is used, and how it can improve efficiency in the operating room. Abstract : Supplemental Digital Content is available in the text.